RANCANG BANGUN MOBILE APP AKSARANESIA.CO BERBASIS ANDROID MENGGUNAKAN WATERFALL MODEL SEBAGAI MEDIA PROGRAM GERAKAN LITERASI SEKOLAH DI SMP NEGERI 4 KOTA YOGYAKARTA - Vitachurrohma Ahsanu Amalah; Windasari (Edu Learning : Journal of Education and Learning, 2024)
This research aims to achieve the following objectives: (1) analyze the validity of the Aksaranesia.co mobile app as a medium for the School Literacy Movement at SMPN 4 Kota Yogyakarta; (2) assess the compatibility of the Aksaranesia.co mobile app as a medium for the School Literacy Movement at SMPN 4 Kota Yogyakarta; (3) evaluate the usability of the Aksaranesia.co mobile app as a medium for the School Literacy Movement at SMPN 4 Kota Yogyakarta. The research follows the Research and Development (R&D) approach. The chosen model is the waterfall, which consists of 5 stages: requirements and definition, system and software design, implementation and unit testing, integration and system testing, and operation and maintenance. The results are as follows: (1) Aksaranesia.co achieved a mean score of 3.30 in content validity testing and 3.66 in construct validity, indicating high validity; (2) Compatibility testing on Android versions 10.0, 11.0, 12.0, and 13.0, as well as using Google Developer (Godev) tools, demonstrated that Aksaranesia.co is 100% compatible; (3) Usability testing yielded a 96.68% rating, indicating that Aksaranesia.co is highly suitable. The application is expected to contribute to the development of literacy media, aligning with the Sustainable Development Goals (SDGs) 2030.